Crystallization Kinetics of Lithium Carbonate in a Continuous Stirred-Tank Crystallizer - Pao-Chi Chen; Jyun-Hong Jhuang; Chung-En Tseng; Zhong-Yi Lin (Crystals)
Lithium carbonate is an important material in the lithium battery. The materials can be obtained from a reactive crystallization process. To prepare the higher-quality crystals, such as purity, crystal size distribution, and desired morphology, it needs to be controlled effectively in the crystallization process. Therefore, a study of crystallization kinetics was required. Here, the metastable region was explored first. Subsequently, a LiCl-K2CO3-H2O reaction system in a continuous stirred-tank crystallizer with controlling pH was used to study the crystallization kinetics, such as nucleation rate (B0), agglomeration kernel (β), and crystal growth rate (G), which can be determined with measured crystal size distribution at a steady-state condition using an agglomeration population balance model. The process variables include lithium chloride solution flow rate, potassium carbonate solution flow rate, and stirring speed. The results show that B0, β, and G were in the range of 3.47 × 109–5.98 × 1012 no/m3·s, 1.78 × 10−19–1.20 × 10−12 m3-slurry/no·s, and 3.00 × 10−11–2.11 × 10−10 m/s, respectively, depending on the operating conditions. All relative supersaturations were in the range of 1.22–2.04. In addition, the crystal size observed was found to be in the range of 1.28–32.7 μm, with irregular platelet forms in most cases. In addition, more slurry density can be obtained at the feed rate of 40 mL/min. A linear regression for crystallization kinetics was also discussed in this work. Finally, this process demonstrated that the recycling of lithium was possible for a circular economy. Therefore, the result can be used as a reference for larger-scale operations in industry.